2009
DOI: 10.1128/jvi.02433-08
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus Activates Transforming Growth Factor β and Bone Morphogenetic Protein Signaling Pathways in the Central Nervous System That Contribute to Neuronal Survival following Infection

Abstract: Viral infections of the central nervous system (CNS) are important causes of worldwide morbidity and mortality, and understanding how viruses perturb host cell signaling pathways will facilitate identification of novel antiviral therapies. We now show that reovirus infection activates transforming growth factor ␤ (TGF-␤) and bone morphogenetic protein (BMP) signaling in a murine model of encephalitis in vivo. TGF-␤ receptor I (TGF-␤RI) expression is increased and its downstream signaling factor, SMAD3, is acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In contrast to the proapoptotic effects of NF-κB and c-Jun, reovirus-induced activation of signal transducer and activator of transcription (STAT) 1 and members of the SMAD family of transcription factors appear to be protective (Beckham et al , 2009; Goody et al , 2007). Thus mice lacking the STAT1 gene demonstrate increased susceptibility to reovirus infection, with increased mortality and higher viral titers in the brain compared to wild-type animals (Goody et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the proapoptotic effects of NF-κB and c-Jun, reovirus-induced activation of signal transducer and activator of transcription (STAT) 1 and members of the SMAD family of transcription factors appear to be protective (Beckham et al , 2009; Goody et al , 2007). Thus mice lacking the STAT1 gene demonstrate increased susceptibility to reovirus infection, with increased mortality and higher viral titers in the brain compared to wild-type animals (Goody et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus mice lacking the STAT1 gene demonstrate increased susceptibility to reovirus infection, with increased mortality and higher viral titers in the brain compared to wild-type animals (Goody et al , 2007). Similarly, treatment of mice with an inhibitor of transforming growth factor-β receptor 1 (TGF-β R1) resulted in increased apoptosis within the brain as demonstrated by increased cleavage of caspase 3 and poly (ADP-ribose) polymerase (PARP) (Beckham et al , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Other viruses induce activation and secretion of TGF-␤. The influenza virus protein neuraminidase directly activates latent TGF-␤ (54), and reovirus and hepatitis C activate TGF-␤ signaling (4,29). It has recently been reported that RSV infection of epithelial cells induces secretion of TGF-␤1 and that treatment of RSV-infected cultured cells with TGF-␤ 12900 THORNBURG ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in neonatal mice, BMP signaling is a normal part of the protective innate immune response against viral infection of the central nervous system. 15 Although abnormal BMP-2 expression has been noted in lung, breast, colon, prostate, and pancreatic cancers, so far BMPs appear to be safe in clinical use. Golden et al noted that in 2043 patients who were each followed for a mean of 2.2 years, the ratio of the observed rate of later malignancy to the expected rate did not indicate an increased risk of malignancy with the use of BMP.…”
Section: Bugs Bone and Biomaterialsmentioning
confidence: 99%